Pengaruh Biaya Produksi dan Harga Jual terhadap Omset Penjualan Telur : (Studi Kasus di CV Tani Ternak Ngudi Rahayu Pati) - Yunike Ameliasari; Ahmad Dwi Nurdiyanto (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study: 1). To determine the effect of production costs on sales turnover, 2). To determine the effect of selling prices on sales turnover, 3). To determine the simultaneous effect of production costs and selling prices on sales turnover. This study was conducted by sampling, with purposive sampling technique, with saturated sampling. The analysis technique used was multiple linear regression, descriptive statistical methods, multiple linear regression analysis, and hypothesis testing. The results of the study can be concluded that: 1). Production costs have a significant effect on sales turnover, 2). Selling prices have a significant effect on sales turnover, 3). Production costs and selling prices have a simultaneous effect on sales turnover.